Audit Energi dan Analisis Peluang Penghematan Energi Listrik Pada Bagian Produksi di PT. EPFM Makassar - Jamal Jamal; Marlina Marlina; Floransya Dwi (Politeknik Negeri Ujung Pandang, 2019)
Basic electricity tariffs that continue to increase force various parties to race to carry out savings programs, the right thing to apply the savings program is energy management and one of them is an energy audit. The energy audit carried out in this study was an energy audit at PT. Makassar EPFM. The energy audit starts with the collection and processing of energy consumption data at the factory, calculates the Energy Consumption Intensity (IKE). From the results of the calculation of the intensity of energy consumption it is known that the level of efficiency in the use of electrical energy in the building. The efficiency of electricity consumption at PT. EPFM can be improved